Tourism, built environment and inclusive landscape - Zen, Ismawi (IIUM Press, 2011)
History makes alive a seemingly dead built environment. The knowledge of it not only enlightens but more importantly it makes the environment exudes a sense of inclusivity; the inclusive landscape. Tourism and built environment are two of a kind; they depend, in fact, feed on one another. Tourism may be just a leisurely activity of being away from the mundane of everyday life: to take in fresh air and to enjoy the view of nature. However, more and more tourism activities are now knowledge-oriented. Built environment evolved with the evolution of man and his civilization. Many are not accessible to tourists, especially those considered as people-withdisability (PwDs). While it is simple to take measures to open up accessibility to new buildings, either from design stage or even after commissioning, the need to preserve the historical integrity of an element of a historic built environment poses a real challenge.